(untitled) (Texas Journal of Philology, Culture and History, 2023)
The resurgence in the use of literature in language teaching has been accompanied by an increasing number of research articles in this area. Research (in a number of second languages) has looked at the type of interactions and the type of language that arise from classroom discussions about literature, as well as at the views of teachers and learners. Importantly, the reactions that learners have to incorporating literature in their language lessons are linked to the type of approach and type of task that are used in the classroom. The paper surveys the existing research, as well as evidence from practitioners about approaches that are used and the range of works and authors that are taught